Translanguaging and positioning in two-way dual language classrooms: a case for criticality. (2nd January 2018) - Hamman, Laura
ABSTRACT: This article examines the role of translanguaging practices and pedagogies in two-way dual language classrooms. Much of the recent expansion of dual language programs across the US has occurred in mid-sized cities and rural communities where English monolingualism is the norm; however, the extant literature on flexible language practices in bilingual learning spaces has largely ignored the implications of translanguaging in these contexts. This case study of a Midwestern dual language classroom provides evidence that flexible language practices can both bolster and hinder the aims of two-way programs. Drawing from these findings, I argue for the creation of a critical translanguaging space, a sociolinguistic learning environment that interrogates micro- and macro-level power flows in the classroom and establishes strategic spaces for language use.